Novel Millet-Based Flavored Yogurt Enriched With Superoxide Dismutase - Fan, Xiankang; Li, Xiefei; Zhang, Tao; Guo, Yuxing; Shi, Zihang; Wu, Zhen; Zeng, Xiaoqun; Pan, Daodong (Frontiers in Nutrition, 2022)
In this study, novel millet-based flavored yogurt enriched with superoxide dismutase (SOD) was developed. Lactobacillus plantarum subsp. Plantarum was screened, which produced SOD activity of 2476.21 ± 1.52 U g -1, and the SOD content of millet yogurt was 19.827 ± 0.323 U mL -1, which was 63.01%, 50.11%, and 146.79% higher than that of Bright Dairy Yogurt 1911, Junlebao, and Nanjing Weigang, respectively. In addition, the T-AOC of millet yogurt was 25.331±1.691 U mL -1, which was 19.86%, 8.67%, and 27.24% higher than that of Bright Dairy Yogurt 1911, Junlebao, and Nanjing Weigang, respectively. A total of 54 volatile flavor substances and 22,571 non-volatile flavor substances were detected in yogurt. Thirty-seven non-volatile metabolites in yogurt with millet enzymatic fermentation broth were significantly upregulated, including 2-phenylethanol, hesperidin, N-acetylornithine, and L-methionine, which were upregulated by 3169.6， 228.36, 271.22, and 55.67 times, respectively, thereby enriching the nutritional value of yogurt. Moreover, the production of unpleasant volatile flavor substances was masked, making the product more compatible with consumers’ taste.